Etiology of diarrhea among children under the age five in China: Results from a five-year surveillance. Issue 1 (July 2015) - Yu, Jianxing; Jing, Huaiqi; Lai, Shengjie; Xu, Wenbo; Li, Mengfeng; Wu, Jianguo; Liu, Wei; Yuan, Zhenghong; Chen, Yu; Zhao, Shiwen; Wang, Xinhua; Zhao, Zhuo; et al.
Summary Objectives Diarrhea is a leading cause of morbidity and mortality for children, although sparse data is available on the etiology of diarrhea in China. This study was conducted to determine main causes that underlie childhood diarrhea and related diseases. Method Surveillance data for diarrhea was collected from 213 participating hospitals between 2009 and 2013. These stool specimens, from children aged 0–59 months, were then analyzed for a panel of etiological agents consisting of 5 viruses, 8 bacteria and 3 protozoa. The proportion of children who tested positive for each pathogen was calculated and seasonal patterns for major organisms were determined. Results Pathogens were identified in 44.6% of the 32, 189 samples from children with diarrhea. The most commonly detected pathogens were rotavirus (29.7% of cases), norovirus (11.8%), Diarrheagenic Escherichia coli (DEC; 5.0%), adenovirus (4.8%), non-typhoidal Salmonella (NTS; 4.3%), and Shigella spp. (3.6%). A strong seasonal pattern was observed for these organisms, including rotavirus (winter), norovirus (autumn), and DEC, NTS, and Shigella (summer). Conclusion A wide range of enteropathogens were detected in this five-year surveillance study; rotavirus and norovirus were most common among children under the age five. These findings should serve as robust evidence for public health entities when planning and developing national intervention programs in China.